Smart Lattice Structures with Self-Sensing Functionalities via Hybrid Additive Manufacturing Technology - He, Liu; Wang, Peiren; Yang, Junhui; Fan, Kaoyi; Zhang, Hanqiang; Zhang, Luyan; Jiang, Mingxing; Chen, Xiaoyi; Chen, Zhen; Chen, Min; Liu, Haiyun; Li, Ji (Micromachines (Basel), 2023)
Lattice structures are a group of cellular materials composed of regular repeating unit cells. Due to their extraordinary mechanical properties, such as specific mechanical strength, ultra-low density, negative Poisson’s ratio, etc., lattice structures have been widely applied in the fields of aviation and aerospace, medical devices, architecture, and automobiles. Hybrid additive manufacturing (HAM), an integrated manufacturing technology of 3D printing processes and other complementary processes, is becoming a competent candidate for conveniently delivering lattice structures with multifunctionalities, not just mechanical aspects. This work proposes a HAM technology that combines vat photopolymerization (VPP) and electroless plating process to fabricate smart metal-coated lattice structures. VPP 3D printing process is applied to create a highly precise polymer lattice structure, and thereafter electroless plating is conducted to deposit a thin layer of metal, which could be used as a resistive sensor for monitoring the mechanical loading on the structure. Ni-P layer and copper layer were successfully obtained with the resistivity of 8.2×10−7Ω⋅m and 2.0 ×10−8 Ω⋅m, respectively. Smart lattice structures with force-loading self-sensing functionality are fabricated to prove the feasibility of this HAM technology for fabricating multifunctional polymer-metal lattice composites.